2016
DOI: 10.17795/ijcp-4080
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Hardiness and Marital Satisfaction in Predicting Posttraumatic Growth in a Sample of Women With Breast Cancer in Isfahan

Abstract: BackgroundPosttraumatic growth (PTG) refers to positive psychological change experienced as a result of the struggle with highly challenging life circumstances. PTG in cancer survivors is related to several psychosocial factors such as psychological hardiness and marital satisfaction.ObjectivesThe purpose of this study was to examine the prediction of posttraumatic growth based on psychological hardiness and marital satisfaction.Patients and MethodsA total of 120 women with breast cancer were recruited from se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 27 publications
1
24
0
2
Order By: Relevance
“…It has been demonstrated that patients with breast cancer are exposed to psychiatric symptoms and psychosocial issues, which may cause mental and social disorders affecting their lives [9][10][11]. Personality characteristics of women with breast cancer, like psychological hardiness, determine the side effects of stressful life events [11][12][13]. Psychological hardiness consists of three basic interrelated hypothetical components.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that patients with breast cancer are exposed to psychiatric symptoms and psychosocial issues, which may cause mental and social disorders affecting their lives [9][10][11]. Personality characteristics of women with breast cancer, like psychological hardiness, determine the side effects of stressful life events [11][12][13]. Psychological hardiness consists of three basic interrelated hypothetical components.…”
Section: Introductionmentioning
confidence: 99%
“…People with a high level of hardiness are possibly more capable of enduring the negative results of life stressors. Their resistance to illness likely results from perceiving life changes as less stressful events or from having more capacity to cope with life changes [13]. Hardiness has a positive relationship with mental welfare [16] associated with using the problem-oriented comparative strategies [17] and attention to positive events of life [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the present study, Rahimi and Heidarzadeh (13) study in patients with myocardial infarction and Heidarzadeh et al (34) study in cancer patients reported the highest growth in the domain of spiritual change and the least growth in the domain of new possibilities. On the other hand, Aflakseir et al (39) in women with breast cancer and Teodorescu et al (40) in Norwegian immigrants concluded that the lowest posttraumatic growth was in the domain of new possibilities. The contradictory results of studies concerning the scores of different domains of posttraumatic growth in different events and societies can be reasonably expected due to differences in the type and quality of the experienced stress, cultural differences, religious teaching, and values of each society that requires further in deep examination using a qualitative approach.…”
Section: Discussionmentioning
confidence: 98%
“…Among these, important personality characteristics such as hardiness and optimism can effectively deal with stress and prevent disease. [ 8 9 ] Hardiness is defined as a combination of beliefs about self and the world, which comprises three components of commitment, control, and militancy. [ 10 ] The concept of hardiness must not be summarized only in special forces for withstanding a lot of stress.…”
Section: Introductionmentioning
confidence: 99%